Light-induced photoactivation of hypericin inhibits cellular growth in pituitary adenoma cell line AtT20/D16v-F2 (hypericin inhibits cellular growth of AtT20/D16v-F2) - Mareková, M; Vávrová, J; Vokurková, D; Cerman, J (Acta medica (Hradec Kralove), 2001)
Cultivation with 4-8 mumol/l hypericin (specific proteinkinase C inhibitor) activated by light induced high inhibition of the rate of HL-60 cell growth. When hypericin treated cells were not exposed to light growth inhibition was insignificant. Cultivation with light activated hypericin in concentration 16 mumol/l slightly inhibited growth rate of AtT20/D16v-F2 cells. AtT20/D16v-F2 cells did not proliferate in presence of light activated 32 mumol/l hypericin. Evidence of apoptosis was found in HL-60 cells treated with 1-8 mumol/l light activated hypericin, with maximum of apoptotic cells detected after 8 mumol/l light activated hypericin. Light activated hypericin induces both apoptosis and necrosis in dose and time dependent manners in HL-60 cells, but causes only necrosis in AtT20/D16v-F2 cells.
Keywords: Pituitary Neoplasms; buněčné dělení; Animals; DNA nádorová; Adenoma; apoptóza; HL-60 buňky; Anthracenes; DNA, Neoplasm; Apoptosis; Cell Cycle; adenom; lidé; Perylene; Mice; Photosensitizing Agents; nádorové buňky kultivované; perylen; HL-60 Cells; myši; fotosenzibilizující látky; buněčný cyklus; Light; anthraceny; Tumor Cells, Cultured; nádory hypofýzy; zvířata; světlo; Cell Division; Protein Kinase C; vztah dávky záření a odpovědi; proteinkinasa C; Dose-Response Relationship, Radiation; Humans